PENGARUH SERVICESCAPES DAN HEDONIC SHOPPING VALUE TERHADAP KEPUTUSAN PEMBELIAN IMPULSIF PADA KONSUMEN WANITA DI GIANT HYPERMARKET MALL OLYMPIC GARDEN (MOG) MALANG - Sari, Larasati Ayu Sekar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to analyze the pattern of relationships by knowing the direct influence of servicescapes and hedonic shopping value against impulse buying behavior at Giant Hypermarket Mall Olympic Garden (MOG) Malang. To find out how much influence the dependent variable (impulse buying behavior) to the independent variables (servicescapes and hedonic shopping value) used regression analysis with analytical methods test t and f. This study uses a sample of 130 women consumers from Giant Hypermarket Mall Olympic Garden (MOG) Malang. While sampling using purposive sampling techniques. The results of studies using multiple linear regression analysis, showed that simultaneous variable servicescapes (X1) and hedonic shopping value (X2) has a significant influence on impulse buying behavior (Y). While partial, variable servicescapes and hedonic shopping value showed a significant effect on impulse buying behavior. Â Keywords: Servicescapes, Hedonic Shopping, Impulse Buying.